Adaption of History Text to Film: Comparative Study of Text Sejarah Kerajaan Melayu Patani into Film Queens of Langkasuka: (Adaptasi Teks Sejarah kepada Filem: Kajian Bandingan Teks Sejarah Kerajaan Melayu Patani kepada Filem Queens of Langkasuka) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2020)
Queens of Langkasuka is a film adaptation of the historical text entitled Sejarah Kerajaan Melayu Patani. The eminence of the female rulers of Patani is noteworthy, and has resulted in this film adaptation. The question is whether the facts and events in the film are as reflected in the original source, or if there have been any additions or omissions, and what of the original has been maintained. Therefore, the main objective of this study is to compare the film Queens of Langkasuka with the text of Sejarah Kerajaan Melayu Patani to view the extent of similarity between the film and the historical text. The second objective is to examine the adaptation techniques used by the director. To this end, adaptation theory was used to identify anything that has been added, removed or retained. This study was conducted using a qualitative method for text and film analysis and comparison, and it finds that all three adaptation techniques were used by the director and scriptwriters in the film Queens of Langkasuka. Comparison reveals that while much was added, much was also discarded and replaced or intentionally modified. Thus, Queens of Langkasuka is a successful work of art that is distinct from the historical text on which it is based.Keywords: Sejarah Kerajaan Melayu Patani, Queens of Langkasuka, Patani, history, adaptation